Effect of water deficiency on growth and dry matter yield of selected in Robusta coffee (Coffea canephora) clones in Malaysia - Tesfaye, S. G.; Ismail, M. R.; Ramlan, M. F.; M., Marziah; Kausar, H.; Hakim, M. A. (Triveni Enterprises, 2015)
Drought stress is one of the major bottle necks of growth and productivity of Robusta coffee (Coffea canephora pierre ex froehner) in many producing areas the crop. An experiment was carried out to determine the difference among known Robusta coffee clones for rate of vegetative growth and dry matter production and partitioning under water deficit stress condition and to identify drought tolerant materials. Twelve-month-old seedlings of six Robusta coffee clones (IC-2, IC-3, IC-4, IC-6, IC-8 and R-4) were subjected to two irrigation treatments: well-watered control and water-stressed by withholding irrigation for 3 weeks in a rain shelter. Growth response to soil drying and dry matter distribution among plant parts were measured to identify drought tolerant clones. Leaf growth of all the coffee clones was considerably affected by soil drying. There were significant differences noted between clones for the rate of reduction in leaf elongation, total leaf area, specific leaf area (SLA) and dry matter yield under water stress condition. Moreover, rate of survival of coffee plants during drought and recovery upon re-watering at the end of the soil drying period significantly varied with clone. Some of the clones, particularly IC-3 and IC-6, exhibited higher root: shoot ratio (0.493-0.613) and total leaf area (900-920cm2) and lower SLA (82-83cm2/g) and rate of leaf fall (62-71 %) than the other clones (with the respective values of 0.413 - 0.447,160 -440cm2, 92 - 97 cm2/g, 82 - 92%) under water-stressed condition. These clones (86 - 88%) survived stress and produced new leaves and flowers more rapidly after re-watering than R-4 (37%) and IC-8 (53%). Hence, clones IC-6 and IC-3 exhibited better performances and seemed to be less sensitive to water deficit stress. Drought tolerance attributes in these clones could be linked to some morphological modifications, mainly increased root: shoot ratio and reduced SLA.